Inversion of multiple geophysical data sets using petrophysical constraints - Kieu, Duy Thong (Curtin University, 2018)
The inversion of multiple geophysical datasets co-operatively is a challenge that I address with the fuzzy cluster method. Techniques to incorporate petrophysical constraints and other data in a robust manner in seismic and magnetotelluric inversion were devised and tested upon synthetic data, and real datasets from Nevada, USA and Kevitsa, Finland. The resulting earth models were demonstrated to be better than with smooth constrained approaches and produced useful outputs for exploration and mining.